Elaboração de itinerários turísticos : Abordagem heurística de um caso real - Colaço, Susana Gueifão (2009)
The problem of Tourist Routes Design involves defining circuits for a tourist wishing to enjoy a several days visit, in a given region following his particular interests. From an Operations Research standpoint, this problem can be framed as a vehicle routing problem with time windows. Once the issue has been analysed, mathematical formulations are drawn up. The methodology proposed is based on a breakdown of the problem into three levels: the first involves determining single day routes (sub-routes), the second, built from the daily sub-routes, concerns a global route whose duration d is decided by the tourist and the third one is designed to obtain an improved global route of d days. For the first level, two constructive heuristics will be presented - a nearest neighbour heuristic and an insertion heuristic. For the second level, a constructive heuristic was created and, for the third, an improvement heuristic embedding diversification-intensification strategies. The algorithms developed were computationally implemented and tested by building tourist routes for the Santarem region.